Translation of terms – the second level of discourse (Eurasian Journal of Philology Science and Education, 2015)
In article are considered a problem of a translational terminoobrazovaniye from the point of view of the second level of a discourse. Translate borrowed terms in Kazakh language requiressophisticated cognitive process. As an example term "proposition" translation process on the Kazakh language is offered. Concepts which are related to translational activity in lexico-semantic aspect as the name, sense, a definition, theexplanation, motivation are also considered. We deny the fact of impossibility of translation of all linguistic terms the Kazakh language. However use in the initial not changed form of linguistic terms as result ofprimary discourse, not deep understanding and perception the sender as the coded semantic sign, considerably limits process of thinking and dynamic development of language. This results from the fact that exhaustive the understanding of any term can be reached through knowledge of zneacheniye of several terms. Finding of the equivalents opening the plan the contents in the native language of these or those terms is, in turn, the creative research which have a direct bearing on development of scientific style and well promoting improvement of quality of a kazakhoyazychny scientific discourse.
Keywords: words; discourse; professional language personality; proposition; name; concept; explanation; interpretation; definition; motivation; vocabulary entry; semantics; an invariant.